Moral status and the wrongness of paternalism - Birks, D (Philosophy Documentation Center, 2014)
In this paper, I consider the view that paternalism is wrong when it demeans or diminishes the paternalizee’s moral status (the Moral Status Argument). I argue that we should reject the Moral Status Argument because it is both too narrow and too broad. It is too narrow because it cannot account for the wrongness of some of the most objectionable paternalistic interventions, namely strong paternalistic interventions. It is too broad because it is unable to distinguish between wrongful paternalistic acts that are plausibly considered more wrong than other wrongful paternalistic acts.